Everolimus induced pulmonary thromboembolism after kidney transplantation; a case report - Fereshteh Saddadi; Mohammad Hassan Fallahkohan (Society of Diabetic Nephropathy Prevention, 2022)
Choice of maintenance immunosuppressive therapy after renal transplantation is important for graft survival. However, complication may also occur. Venous thromboembolic event with the mTOR inhibitor (mTORi) everolimus is a rare but life-threatening complication. Here we describe a renal transplant recipient who developed pulmonary thromboembolism.